Interpretasi Bawah Permukaan Daerah Manifestasi Panas Bumi Parang Tritis Kabupaten Bantul DIY Dengan Metode Magnetik - Indratmoko, Putut; Nurwidyanto, M. Irham; Yulianto, Tony (BERKALA FISIKA, 2009)
Abstract Acquisition of geomagnetic field has been done at Kretek, Sanden, Pundong, Bantul and Panggang, Gunung Kidul, Yogjakarta Province on 14 s/d 17 October and 7,8,9,12 November 2009 in orde to interpreted the subsurface structure. Data has been collected by Proton Precession Magnetometer (PPM) to measured the total intensity of magnetic field, Global Positioning System (GPS) to determine the position and geology compass to the direction of north pole. The raw data has been processed and performed using IGRF (International Geomagnetics Reference Field) correction to obtain total field magnetic anomaly. Upward continuation was performed at 300 meters heigh by Magpick. Qualitative interpretation was done by analyzing regional and local anomaly maps. Quantitative interpretation was done 2 ½ D modelling cross-sectionanomaly maps using Mag2DC for Windows Software. The result of 2-D modeling produces anomaly objects was susceptibility value (0,0405) in cgs unit for the first object, susceptibility value (0,0425) in cgs unit for the second object, susceptibility value (-0,0085) in cgs unit for the third object. The anomaly objects had depth in +580 meters from the surface and was considered the rock which had been experience demagnetitation proses. Key word: magnetic anomaly, Parangtritis, susceptibilities.